Description of Thrombopheresis Blood Donor at UDD PMI Yogyakarta City in 2021 - Almira Zhafirah; Christina Roosarjani; Betty Prasetyaswati; Kunti Dewi Saraswati (International Journal of Seocology, 2023)
Thrombopheresis is donor apheresis to collect platelet blood components. One apheresis platelet donor bag is equivalent to 6-10 regular platelet donor bags. The study aims to determine the profile of thrombopheresis of blood donors at the Blood Donation Unit (BDU) of Indonesian Red Cross Yogyakarta City in 2021. This study uses a quantitative descriptive research design with a cross sectional approach. The population was all thrombopheresis blood donors at BDU of Indonesia Red Cross Yogyakarta City in 2021. The sample was 52 thrombopheresis. Data collection using secondary data processed using SPSS and Microsoft Excel. Univariate data analysis in the form of tables, diagrams and descriptions. Based on data there are 52 voluntary donors (100%). Based on gender, there are 43 males (82.7%) and 9 females (17.3%). Based on age there are 18-24 years old 3(5.8%), 25-44 years old 27 (51.9%), 45-64 years old 21 (40.4%) and 65 years old 1 (1.9%). Based on blood group, group A rhesus positive 7 (13.5%), group B rhesus positive 9 (17.3%), blood group O rhesus positive 36 (69.2%), blood group AB rhesus positive 0 (0%). Blood donation thrombopheresis were carried out mostly by voluntary donors, male, age 25-44 years old and blood group O Rhesus positive at Blood Donation Unit (BDU) of Indonesian Red Cross Yogyakarta city in 2021.